An overview of the past, current and future trends for cervical ripening in induction of labour. (July 2017) - Chodankar, Rohan; Sood, Akanksha; Gupta, Janesh
Abstract : Key content: The advantages and disadvantages of pharmacological methods and mechanical methods (such as the osmotic cervical dilator Dilapan‐S ® and Foley catheter) for labour induction are discussed. This article looks at the international and local (UK) experience with use of Dilapan‐S ® for cervical ripening. The Cochrane and Royal College of Gynaecologists and Obstetricians (RCOG) statements with regards to use of mechanical dilators are referenced. Learning objectives: To know the past, current and future trends in cervical ripening for labour induction. To understand that mechanical methods (e.g. Dilapan‐S ® and Foley catheter) offer similar efficacy and better safety compared to PGE2.